A data-driven evaluation of the grant program for excellence in learning and teaching (PELT): AI-leveraged insights from faculty, students, and academic metrics - Shahba, Ahmad Abdul-Wahhab; Alkathiri, Saud; Alsadoon, Elham; Soufan, Walid (Frontiers in Education, 2025)
BackgroundThe landscape of higher education is evolving with an emphasis on teaching excellence and student-centered learning, driven by technological advancements and societal changes. This study aimed to comprehensively evaluate the impact of the grant Program for Excellence in Learning and Teaching (PELT) at King Saud University, the first of its kind in Saudi Arabia.MethodsUsing a mixed-methods approach, the research design combined quantitative and qualitative data collection and analysis techniques. Faculty and student surveys were conducted to assess the program’s impact on teaching practices, student engagement, and skills development. Additionally, student academic performance data, including self-reported PELT course grades and university-reported final exam scores, were analyzed. The study examined the influence of various factors, such as academic discipline and grant theme on the program’s outcomes. Textual feedback from faculty and students was subjected to AI-assisted thematic and sentiment analysis to uncover key themes and insights.ResultsThe PELT program showed a positive impact on faculty’s pedagogical skills, teaching methods, and perceptions of student learning. Faculty members showed a stronger preference for the “Student Professional Development” grant theme, while students valued the “Curriculum and Course Content Development” and “Excellence in Teaching and Assessment Strategies” themes more. The student textual feedback highlighted the need for more dynamic, student-focused, and practically oriented educational approaches. The innovative use of AI-powered sentiment analysis offered valuable complementary insights into student experiences, complementing the traditional survey-based methods. The analysis of student-reported academic performance revealed that PELT course grades were slightly higher than overall GPA, with the Humanities discipline demonstrating significant positive impacts. Importantly, the university-reported score analysis further highlighted that courses emphasizing student-faculty interactions and student-professional development (T2 and T3 themes) showed significantly higher scores in the PELT group compared to the control group, while the T1 (Curriculum and Course Content Development) theme showed the opposite.ConclusionThe study’s findings underscore the importance of aligning educational interventions with approaches that prioritize active learning, collaborative experiences, and authentic student-faculty interactions. Furthermore, this study provides a robust foundation for assessing the impact of faculty development programs and guiding data-driven decisions to enhance the quality of higher education.